Mortality in Levodopa-Treated Parkinson's Disease - John C. Morgan; Lillian J. Currie; Madaline B. Harrison; James P. Bennett; Joel M. Trugman; G. Frederick Wooten (Parkinson's Disease)
Parkinson’s disease (PD) is associated with increased mortality despite many advances in treatment. Following the introduction of levodopa in the late 1960’s, many studies reported improved or normalized mortality rates in PD. Despite the remarkable symptomatic benefits provided by levodopa, multiple recent studies have demonstrated that PD patients continue to die at a rate in excess of their peers. We undertook this retrospective study of 211 deceased PD patients to determine the factors associated with mortality in levodopa-treated PD. Our findings confirm that PD is associated with increased mortality in both men and women. Unlike the majority of other mortality studies, we found that women have a greater reduction in lifespan compared to men. We also found that patients with early onset PD (onset at the age of 50 or before) have reduced survival relative to PD patients with later ages of onset. A final important finding is that survival is equal in PD patients treated with levodopa early (within 2 years or less of PD onset) versus later.